Promoting role of Electronic Commerce on Economic Growth - Weiyue, LIU (Archives of Business Research, 2017)
In recent years, China becomes an important force and focus in the international e-commerce market due to its strong development momentum in the field of electronic commerce. E-commerce has changed the development way of the national economy and people’s life style. With this change, the social efficiency are improved greatly. With the expansion of information access, increase to information quantity and improvement of the information processing ability, e-commerce impacts heavily on macro and micro economic environment, reduces the uncertainty of economic activity, ensures the timely application of information, reduces the cost of access to information, improves the efficiency of economic activity, and finally makes higher efficiency of the allocation mechanism for the market resource.